1999
DOI: 10.1002/(sici)1099-1077(199908)14:6<415::aid-hup95>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ephedrine on the development of fatigue in a prolonged driving-related task

Abstract: The eects of ephedrine on the development of fatigue in a prolonged driving-related task were investigated using three independent measures. Subjects (n 15) received either ephedrine (60 mg) or a placebo before carrying out a 3-way divided attention task for an uninterrupted 4 h period, during which cardiac inter-beat interval was monitored. A battery of psychomotor tests and two questionnaires were completed before and after the 4 h session and oral temperature, blood pressure and heart rate were also recorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…This occurred, in part, because the FDA received many reports of serious adverse events resulting from the consumption of ephedra-containing products (FDA 1997;Shekelle et al 2003). Few behavioral studies have examined the effects of ephedra or ephedrine on cognitive performance and mood, although ephedrine had stimulant-like effects on vigilance in a task designed to simulate prolonged operation of a motor vehicle and increases subjective alertness, as assessed by mood questionnaires (Mooleenar et al 1999).…”
Section: Nutrients Food Constituents and Dietary Supplements That Mmentioning
confidence: 99%
“…This occurred, in part, because the FDA received many reports of serious adverse events resulting from the consumption of ephedra-containing products (FDA 1997;Shekelle et al 2003). Few behavioral studies have examined the effects of ephedra or ephedrine on cognitive performance and mood, although ephedrine had stimulant-like effects on vigilance in a task designed to simulate prolonged operation of a motor vehicle and increases subjective alertness, as assessed by mood questionnaires (Mooleenar et al 1999).…”
Section: Nutrients Food Constituents and Dietary Supplements That Mmentioning
confidence: 99%
“…A single 60 mg dose of ephedrine maintains focus during a driving-related task (Moolenaar et al, 1999). The major active ingredients are ephedrine and pseudoephedrine, stimulants that raise blood pressure and heart rate.…”
Section: Centella Asiatica Ephedra Sinica and Crocus Sativusmentioning
confidence: 99%
“…Moreover, HRV has been used in a variety of disciplines to diagnose illness and has been found to correlate with severity of illness (Task Force of the European Society of Cardiology and the North American Society of Pacing and Electrophysiology, 1996;Kleiger et al, 2005). Moolenaar et al (1999) reported that the ingestion of ephedrine, the main ingredient of ephedra, is able to change HRV measures in subjects carrying out driving-related task; however, there is no information available regarding the effects of ephedra on HRV. To better understand the actions of ephedra so that the negative effects can be avoided, the present study investigates the effects of ephedra in healthy young adults in terms of their autonomic nervous modulation using power spectral analysis of the HRV as the tool.…”
Section: Introductionmentioning
confidence: 99%